Submarine geomorphology and sea floor processes along the coast of Vestfold Hills, East Antarctica, from multibeam bathymetry and video data. Issue 6 (16th September 2015) - O'Brien, Philip E.; Smith, Jodie; Stark, Jonathan S.; Johnstone, Glenn; Riddle, Martin; Franklin, Dennis
Abstract: A survey of nearshore areas in the Vestfold Hills, Antarctica, using high-resolution multibeam swath bathymetry provided both a detailed digital bathymetric model and information on sediment acoustic backscatter. Combined with underwater video transects and sediment sampling, these data were used to identify and map geomorphic units. Six geomorphic units identified in the survey region include: rocky outcrops, basins, pediments, valleys, scarps and embayments. In addition to geomorphic units, the data revealed sedimentary features that provide insights into post-glacial sediment transport and erosion in the area. Ice keel pits and scours are common, and sea floor channels, scour depressions and sand ribbons indicate transport and deposition by wind-driven currents and oceanographic circulation. Gullies and sediment lobes observed on steep slopes indicate mass movement of sediment. Some of these processes have not been directly observed to date, but their effectiveness in shaping the modern sea floor is clearly indicated by the sea floor mapping data. The embayments preserve a mantle of boulder sand probably deposited by cold-based glaciers which were flanked by faster-flowing ice in adjoining regions.